Pengaturan Prinsip Good Governance dalam Pelayanan Publik di Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Kota Kupang di Tinjau dari Undang-Undang Nomor 25 Tahun 2009 Tentang Pelayanan Publik - Meriyanti Mayesti Bauky; Saryono Yohanes; Hernimus Ratu Udju (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This study aims to find out and analyze the regulation of good governance principles in the Kupang City One-Stop Integrated Service and One-Stop Integrated Service reviewed from Law No. 25 of 2009 concerning Public Services. This type of research is normative legal research, namely legal research conducted by researching literature materials or secondary data, in this case laws and regulations, books and legal journals. The results presented in this study are (1) Regulation of Good Governance Principles where there are five functions carried out by the Kupang City Investment and One-Stop Integrated Services Office (2) Good Governance Principles in Ensuring Legal Certainty and Justice where there are 6 foundations or Governance Principles enforced in the Kupang City Investment and One-Stop Integrated Services Office (3) Implications of the Principle of Good Governance in Public Services where the motto of the Kupang City Investment and One-Stop Integrated Service Office (DPMPTSP) in carrying out licensing service activities is